Ecology of Anopheline (Diptera, Culicidae), malaria vectors around the Serra da Mesa Reservoir, State of Goiás, Brazil: 1 - Frequency and climatic factors Ecologia de Anophelinae (Diptera, Culicidae), vetores de malária em áreas da Usina Hidrelétrica de Serra da Mesa, Estado de Goiás, Brasil: 1 - Freqüência e fatores climáticos - Anthony Érico Guimarães; Carla Gentile; Jeronimo Alencar; Catarina Macedo Lopes; Rubens Pinto de Mello (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2004)
The ecology of anopheline species (Diptera, Culicidae) was studied in the vicinity of the Serra da Mesa Reservoir, State of Goiás, Brazil. Climatic factors and frequency of anopheline populations were analyzed. Bimonthly human-bait and Shannon trap captures were conducted for 36 consecutive months (January 1997 through December 1999). A total of 5,205 adult anophelines belonging to five species were collected. Anopheles darlingi was the most frequently collected anopheline (61.4%), followed by An. albitarsis s.l. (35.4%), An. triannulatus. (2.5%), An. oswaldoi (0.4%), and An. evansae (0.2%). The water level and vegetation along the banks of the reservoir were crucial to the frequency of the various anopheline species. Climatic factors had a secondary influence. The reservoir's water-level stability, increased frequency of An. darlingi, and the arrival of gold prospectors were responsible for the increase in malaria cases. Foram estudados aspectos da ecologia de anofelinos (Diptera, Culicidae) em áreas da Usina Hidrelétrica de Serra da Mesa, Estado de Goiás, Brasil. Foram analisados a incidência das populações de anofelinos e os fatores climáticos. Foram realizadas capturas bimestrais, em isca humana e armadilha Shannon, ao longo de 36 meses consecutivos (janeiro de 1997 a dezembro de 1999). Capturamos um total de 5.205 anofelinos adultos, pertencentes a cinco espécies. Anopheles darlingi foi o anofelino mais freqüente (61,4%), seguido de An. albitarsis s.l. (35,4%), An. triannulatus (2,5%), An. oswaldoi (0,4%) e An. evansae (0,2%). O nível da água e a vegetação às margens do reservatório foram determinantes para a freqüência das espécies de anofelinos. Os fatores climáticos tiveram influência secundária. A estabilidade do reservatório, o aumento na freqüência do An. darlingi e a chegada de garimpeiros foram responsáveis pelos casos de malária diagnosticados.